Ilê Aiyê, de bloco racista à elite negra - Macedo, Márcio (Afro-Ásia, 2025)
Resenha de: AGIER, Michel. Ilê Aiyê: A Fábrica do Mundo Afro (Carnaval da Bahia, 1974-2024), São Paulo: Editora 34, 2024. 176 p.